2019
DOI: 10.5005/jp-journals-10005-1633
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Pediatric Oncology Patients and the Occurrence of Oral Mucositis

Abstract: BackgroundIt is known that chemotherapeutic agents are not equally stomatotoxic and oral cavity lesions are the most frequent complications encountered in antineoplastic chemotherapy.AimsThe objective of this study was to evaluate the occurrence of severe oral mucositis during a chemotherapy treatment and to identify its relationship with the chemotherapeutic class used.Materials and methodsThis is a longitudinal, prospective, and observational study that used an intensive direct observation technique for asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Some specific protocols and each chemotherapeutic agent reported in these protocols for the treatment of some neoplasms are described in Table 3, such as COG AHOD0031 and COG AHOD0831 for the treatment of Hodgkin lymphoma (HL) (Allen et al., 2017), leukemias (BFM‐95) (Figliolia et al., 2008), Burkitt's lymphoma, ALL and Ewing's sarcoma (COPADM, VIDE and multidrug conditioning regimen) (Gandemer et al., 2007), which were also considered to be factors. Other agents, such as daunorubicin, doxorubicin, vincristine, and etoposide (Damascena et al., 2020), busulfan (Fadda et al., 2006), MTX, and cytarabine (Ara‐C) (Ribeiro et al., 2019), were also presented as potential risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Some specific protocols and each chemotherapeutic agent reported in these protocols for the treatment of some neoplasms are described in Table 3, such as COG AHOD0031 and COG AHOD0831 for the treatment of Hodgkin lymphoma (HL) (Allen et al., 2017), leukemias (BFM‐95) (Figliolia et al., 2008), Burkitt's lymphoma, ALL and Ewing's sarcoma (COPADM, VIDE and multidrug conditioning regimen) (Gandemer et al., 2007), which were also considered to be factors. Other agents, such as daunorubicin, doxorubicin, vincristine, and etoposide (Damascena et al., 2020), busulfan (Fadda et al., 2006), MTX, and cytarabine (Ara‐C) (Ribeiro et al., 2019), were also presented as potential risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the younger a patient is, the higher the chances that chemotherapy will cause adverse effects on oral health are ( Cheng et al, 2011 ). The type, dosage, and frequency of chemotherapy drugs may have an impact on the occurrence and severity of OM, especially 5-fluorouracil, cyclophosphamide, cisplatin, and methotrexate; these chemotherapy drugs are involved in the emergence of changes in the oral mucosa ( Ribeiro et al, 2019 ). The result of the combined analysis of CIOM grade showed that, although the included studies were the same, slight differences in heterogeneity between the two studies were found.…”
Section: Discussionmentioning
confidence: 99%
“…However, the chemotherapeutic drugs of choice in the treatment of pediatric cancer are not equally stomatotoxic. MTX and 5-fluorouracil, both antimetabolites, are the drugs most reported to cause alterations in the oral mucosa [8,18]. Patients whose therapeutic regimens do not include MTX tend to have a lower occurrence of SOM [7].…”
Section: Discussionmentioning
confidence: 99%
“…Four classes of chemotherapeutic drugs were considered, according to the classification of the National Health Surveillance Agency, namely: alkylating agents, antimetabolites, natural products and miscellaneous. The present study focused on the class of antimetabolites, particularly methotrexate (MTX), since previous studies have shown that patients under chemotherapy regimen with antimetabolites are more likely to develop SOM [7,8]. MTX is one of the most widely used chemotherapeutic drugs, despite presenting stomatotoxicity and being frequently related to the occurrence of SOM [18].…”
Section: Definiton Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation